Alzheimer's disease : [videorecording (DVD)] facing the facts - Orkin, Glenn; Herrmann, Edward, 1943-2014 (WGBH Boston Video, 2009)
In comparison to cancer, heart disease, and AIDS, Alzheimer's disease greatly lags in research funding, media attention, and celebrity support. Examine the personal and societal implications of this discrepancy, profiling families living with Alzheimer's, interviewing the doctors on the front lines, and scrutinizing the latest research.